2018
DOI: 10.1213/ane.0000000000002542
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Adding Subarachnoid Epinephrine to Hyperbaric Bupivacaine and Morphine for Repeat Cesarean Delivery: A Double-Blind Prospective Randomized Control Trial

Abstract: In this single center, prospective, double-blind, randomized control trial, the addition of epinephrine 200 µg to hyperbaric bupivacaine and preservative-free morphine for repeat cesarean delivery prolonged the duration of the sensory blockade. Motor blockade was similarly prolonged and block quality may have been enhanced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 25 publications
1
8
2
Order By: Relevance
“…“Opioid and α2-adrenoceptor (AR) agonists are analgesic when administered in the spinal cord and show a clinically beneficial synergistic interaction when co-administered”, according to Chabot-Doré et al [ 20 ]. Many other studies have confirmed such an effect for mu and delta OPR as well as for a wide range of adrenergic agonists ranging from amphetamines to clonidine (e.g., [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ]). The enhancement of opioid function by adrenergic agonists, particularly amphetamines, has been observed in other systems as well, such as opioid-mediated reward and related behaviors [ 59 , 60 , 61 , 62 , 63 , 64 , 65 ]; glucose uptake in the brain [ 66 ]; and on guinea pig ileum contractions induced by morphine, which are also enhanced by serotonin [ 67 , 68 , 69 ].…”
Section: Introductionmentioning
confidence: 83%
“…“Opioid and α2-adrenoceptor (AR) agonists are analgesic when administered in the spinal cord and show a clinically beneficial synergistic interaction when co-administered”, according to Chabot-Doré et al [ 20 ]. Many other studies have confirmed such an effect for mu and delta OPR as well as for a wide range of adrenergic agonists ranging from amphetamines to clonidine (e.g., [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ]). The enhancement of opioid function by adrenergic agonists, particularly amphetamines, has been observed in other systems as well, such as opioid-mediated reward and related behaviors [ 59 , 60 , 61 , 62 , 63 , 64 , 65 ]; glucose uptake in the brain [ 66 ]; and on guinea pig ileum contractions induced by morphine, which are also enhanced by serotonin [ 67 , 68 , 69 ].…”
Section: Introductionmentioning
confidence: 83%
“…The most commonly used technique in leg fracture surgery is epidural anesthesia, which provides both perioperative surgical anesthesia and postoperative analgesia. Early postoperative mobilization and rehabilitation along with minimal pain and discomfort are the main objectives of the modern orthopedic surgery (14, 25-27).…”
Section: Discussionmentioning
confidence: 99%
“…Dexmedetomidine as an adjunct directly increases the block time through the direct modulating of receptors on motor neurons and posterior horn sensory neurons of the spinal cord or their synapses (12, 13). The analgesic effects of epidural bupivacaine when administered alone last almost 4 - 6 h, but epidural morphine is effective for 12 - 24 h (14). The comparison of dexmedetomidine and fentanyl as intrathecal adjuvant drugs to bupivacaine showed that dexmedetomidine could prolong motor and sensory blockade and reduce the anesthetics consumption during the initial 24 h post-surgery (15).…”
Section: Introductionmentioning
confidence: 99%
“…Cross-talk between opioid receptors and adrenergic receptors has been well-characterized both in laboratory and clinical studies. Opioid compounds such as morphine and the enkephalins enhance adrenergic receptor activity [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15], while adrenergic compounds such as epinephrine, norepinephrine, and propranolol enhance opioid receptor activity [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. This enhancement is characterized by several unusual characteristics.…”
Section: Introductionmentioning
confidence: 99%